A behaviorist approach to the Brazilian Psychiatric Reform: notes towards a dialog - Lima, Aline Nunes de Santana; Carrara, Kester (Perspectivas em Análise do Comportamento, 2020)
The essay aims to discuss some of the Brazilian Psychiatric Reform’s principles from the point of view of Behavior Analysis and Radical Behaviorism, pointing out some contributions to the field. One of the contributions of Behavior Analysis is the non organicist comprehension of psychiatric illness, which emphasizes the role of environment in the origin and maintenance of these repertoires. Behavior Analysis doesn’t promote coercive methods in the assistance of psychiatric illness and emphasizes the promotion of alternative repertoires. Another contribution from the psychological theory to the Psychiatric Reform is the discussion on the concept of freedom, which is considered a guiding value to the service’s reconfiguration. Freedom in the behavior analytic point of view is a matter of reinforcement contingencies and it is necessary to plan and maintain therapeutic environments which promote autonomy. The behavior analysis of culture can be considered another contribution for the Brazilian Psychiatric Reform as the change of cultural practices can be explored. In this essay we aimed to point out some common points and initial possibilities of dialog between the two areas. Other theoretical and applied researches can be developed to expand this dialog.